Hubungan Penerapan Profil Pelajar Pancasila pada Pembelajaran PPKn dengan Kemandirian Belajar Siswa - Nur Khasanah; Septi Fitri Meilana (Universitas Negeri Makassar, 2022)
This study aims to knowing whether there is a significant relationship between the application of the pancasila student profile in civics learning and student independence. This study was conducted because there are students whose character have not been seen, especially in independence. The method used in this research is correlational quantitative. The sample used was 59 students from all fourth grade students at Public Elementary School Susukan 07 there is IV A and IV B. The research instrument used is a questionnaire containing statements to obtain data on the profile of pancasila students and students learning independence. The data hypothesis used in this study is Pearson Correlation and the result obtained are significant values 0.72 > 0.05, which means there is no significant correlation between the profile of pancasila students in civics learning and student learning independence. The conclusion of this study is because the data obtained is greater than significant level of 0.05, it can be concluded that Hₐ is rejected and H₀ is eccepted.